Análise da implementação do planejamento em universidades públicas federais: o caso da Universidade Federal do Pampa - Costa, Loreno Vaz (2014)
Public Institutions are living an expansion moment with a great financial support to its structuring. Federal Pampa University UNIPAMPA - is in this context, marked by changes. Localized in South of Rio Grande do Sul, the Federal Pampa University is charactherized by its multicampi structure, there are 10 campi: Alegrete, Bagé, Caçapava do Sul, Dom Pedrito, Itaqui, Jaguarão, Santana do Livramento, São Borja, São Gabriel e Uruguaiana. In this sense, to guarantee good results of this region insertion Project, the managers actions have to be based on organizational efficiency and effectiveness principles, and also, to ensure theses actions fullfilment, the university management has to be guided by a strategic planning instrument represented by the Institutional Developing Planning, Decree 5.773/06. Thus, this paper was developed to verify the Institutional Developing Planning efectiveness as an instrument of management in a multicampi University and to identify some possible factors that influenced in its implementation. To fullfil the research objective a case study was the chosen method, set by literature review, documents analysis and a questionnare with 40 questions sent to different managers to obtain quantitatives datas. An analysis of planning methodologies was made, as studies that explain the factors that effects the multicampi universities implementation, to substantiate the reasearch instrument. In this way, the data analysis demonstrated that the Institutional Developing Planning implemantation at UNIPAMPA shows some positive aspects, one aspect that can be highlighted is the IDP recognition as na importante reference tool and its management actions. However there are specific factors related to university oorganizations, as leadership, internal control, and aspects connected to political power, that contribute in a negative way effective IDP action, highlighting that the planning was concieved by the organizational bureaucratic needs, like the accreditation purpose and its thematic axis. Thereby, the strategic planning has a instant connotation to meet some requirements, placing goals and strategies that perhaps are not according to the instition mission.